Innovative Educational Technologies in Teaching Foreign Language - Sanatina M. V., Shuldais Y. A. (Psychological and Pedagogical Support of Talented Children: Problems, Directions, Approaches, Conditions, 2020)
the article deals with the basic innovative educational technologies such as problem-based learning, multilevel training and project training and using research methods, a game-based learning method, information and communications technology and health-saving technologies within the framework of their application. The peculiarities and advantages of their use in foreign language lessons are described.
Keywords: инновация; проблемная ситуация; образовательная технология; innovation; problem situation; educational technology; исследовательские методы; research methods